MINAT ATLET WANITA PADA OLAHRAGA GULAT - Syallomita Elsaday Pompayo; Rostina Uduas; Melky Pangemanan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The purpose of this study is to characterize women's involvement in the martial arts sport of wrestling in the setting of West Javan training centers. This kind of study is called a qualitative descriptive one. Female martial artists who wrestled were the study's subjects. In-depth interviews were used as part of the data gathering approaches to get precise information on the problem's focal point. The study's findings clarify that some phenomena, such as (a) shifts in views from those who once felt inferior or frightened to appear in public to those who now feel more comfortable doing so, are indicative of women who practice the martial arts sport of wrestling. (b) roles in the social space have changed, which used to be inactive in activities or in school organizations or in the village, after participating in the martial arts Wrestling they became more active in activities and in school organizations and in the village, (c) habits change to be more positive, which used to be lazy to exercise, become happy and routinely exercise, (d) and those who used to be embarrassed or embarrassed to mix with men are now not embarrassed and they consider it normal for women to mix with men. There is a negative view from society that considers women incapable and unsuitable to participate in the martial arts sport of Wrestling which is identical to men. Women who follow the martial art of Wrestling respond to it with indifference and feel it is suitable to continue pursuing the martial art of Wrestling to achieve even higher achievements.